The Relationship between VDR Gene Polymorphisms Bsm1 and Apa1 with Breast Cancer Risk - Hengameh Mozaffarizadeh; Fariborz Mokarian; Mansoor Salehi; Seyyed Mohammad Reza Hakimian; Elham Moazam; Amirmohammad Amoozadehsamakoosh; Majid Hosseinzadeh; Mahdieh Behnam; Mohaddeseh Behjati; Alma Naseri; Marzieh Lotfi; Fatemeh Tohidi (Global Medical Genetics, 2024)
Background In addition to its multifaceted physiological functions, vitamin D is recognized for its protective role against cancer. To manifest its effects, vitamin D engages with the vitamin D receptor (VDR) gene responsible for its encoding. Investigations have unveiled that polymorphisms within the VDR gene exert influence over the expression and/or functionality of the VDR protein. Notably, certain VDR gene polymorphisms have emerged as particularly pertinent in the context of tumorigenesis, including Fok1 (rs2228570), Bsm1 (rs1544410), Taq1 (rs771236), and Apa1 (rs7975232). This study aims to scrutinize the correlation between the Bsm1 and Apa1 polymorphisms and the susceptibility to breast cancer development.